2020
DOI: 10.1051/0004-6361/202037718
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of large main-belt asteroids observed byHerschelPACS

Abstract: Non-resolved thermal infrared observations enable studies of thermal and physical properties of asteroids via thermo-physical models provided the shape and rotational properties of the target are well determined. We used calibration-programme Herschel PACS data (70, 100, 160 μm) and state-of-the-art shape models derived from adaptive-optics observations and/or optical light curves to constrain for the first time the thermal inertia of twelve large main-belt asteroids. We also modelled previously well-character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
(68 reference statements)
4
11
0
Order By: Relevance
“…Our larger α and steeper β terms with our sample's data compared to the literature-only data set can be accounted for by the lack of large asteroids in our sample, having only one data point with a diameter larger than 100 km. Though many of the literature estimates we fit use several different thermophysical models and thermal data sources, such as observations from the Spitzer Space Telescope (e.g., Lamy et al 2008;Marchis et al 2012) and the Herschel Space Observatory (e.g., O'Rourke et al 2012;Fornasier et al 2013;Alí-Lagoa et al 2020), we see an overall strong consistency with our Γ-D relation compared to the literature as a whole. Because our thermal inertia error bars are so large, however, it is difficult to draw any more definitive conclusions about its relationship with size.…”
Section: Relationship With Sizesupporting
confidence: 68%
See 1 more Smart Citation
“…Our larger α and steeper β terms with our sample's data compared to the literature-only data set can be accounted for by the lack of large asteroids in our sample, having only one data point with a diameter larger than 100 km. Though many of the literature estimates we fit use several different thermophysical models and thermal data sources, such as observations from the Spitzer Space Telescope (e.g., Lamy et al 2008;Marchis et al 2012) and the Herschel Space Observatory (e.g., O'Rourke et al 2012;Fornasier et al 2013;Alí-Lagoa et al 2020), we see an overall strong consistency with our Γ-D relation compared to the literature as a whole. Because our thermal inertia error bars are so large, however, it is difficult to draw any more definitive conclusions about its relationship with size.…”
Section: Relationship With Sizesupporting
confidence: 68%
“…It is difficult to comment on the average thermal inertia representative of various asteroid subpopulations as existing thermal inertia estimates only number in the few hundreds and cover a wide range in values, from 0 to nearly 1500 J m −2 s −0.5 K −1 (see Table 3). Previous studies have attempted to identify how thermal inertia might correlate with other physical properties such as spectral type, rotation period, and size (e.g., Delbo' et al 2015;Hanuš et al 2018a;Alí-Lagoa et al 2020). Due to the inverse dependency of skin depth with rotation speed, the heat from solar radiation can penetrate the thin topmost regolith layers of slowly rotating asteroids and reach the denser, more highly thermally conductive subsurface material.…”
Section: Introductionmentioning
confidence: 99%
“…It was thus hypothesized that slow rotators (i.e., rotation periods longer than 12 hours) should on average present higher thermal inertia than those of fast rotators. While early studies such as Harris & Drube (2016) and Marciniak et al (2018) appeared to confirm this trend, later studies with larger samples of slow rotators (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) found no such relation.…”
Section: Introductionmentioning
confidence: 95%
“…Numbers in italics mark the pole solution of ( 667 where the α exponent is equal to 0.75, which takes into account a radiative conduction term in thermal conductivity. Different exponents are also possible (Rozitis et al 2018), but here we opted for the most widely used value to facilitate comparison with previous works (see the discussion in Alí-Lagoa et al 2020;Szakáts et al 2020).…”
Section: Resultsmentioning
confidence: 99%